Ergonomics workstation environment toward organisational competitiveness - Zafir Khan Mohamed Makhbul; Md Shafiin Shukor; Ariff Azly Muhamed (International Journal of Public Health Science (IJPHS), 2022)
The lack of comfort due to workplace environment impact could trim down job performance and organizational productivity. Literature reviews indicate that ergonomic workplace environment that is strongly associated with the job performance. Employees’ perceptions to be examined by the organizations to ensure the excellent job performance. Thus, 295 officers were selected using proportionate stratified random sampling with two-section questionnaire. The data were analyzed using statistical package for the social sciences (SPSS) and analysis of a moment structure (AMOS) software. The research findings show that acoustic is the most crucial factor (0.928) followed by lighting (0.898), workstation design (0.846), working hours (0.670), and chair (0.563). Ventilation is still significant to the whole environment although scored the lowest coefficient value (0.385). These findings provide valuable information to organizations in their attempts to sustain the human resources so that they are always competitive and productive in facing the challenges of the environmental change.